(untitled) (MiKAN, 2026)
This article suggests that the novel Temol Shilshom (Only Yesterday) by S. Y. Agnon is a "double novel" ("Doppelroman") whose plot embraces two different and very opposite stories: One relates to the adventures of Isaac Kumer during the Second "Aliyaln" (1903-1914) and is basically a story of rebirth and regeneration; the second is a story of events contemporary with the writing of the novel itself, i.e.. World War II (1939-1945) and is basically a story of destruction. The central argument of this article is that it is necessary to perceive the simultaneous existence of the two stories in order to understand the novel as a whole and to interpret the world-view of its author. The article examines the "double-ness" of the novel while pausing to look at thematic and poetic intersections central to the scholarly discourse on the novel, including the question of fragmentation, the deconstruction of reality, and the nagging question of the relationship between the protagonist, Isaac Kumer, and the story about the dog Balak. By revealing the novel’s covert dialogue between two such foundational periods of history, we discover complex literary mechanisms and an intriguing world-view ofAgnon vis-a-vis literature and history.